2022
DOI: 10.18632/aging.203794
|View full text |Cite
|
Sign up to set email alerts
|

Huangqi Guizhi Wuwu Decoction can prevent and treat oxaliplatin-induced neuropathic pain by TNFα/IL-1β/IL-6/MAPK/NF-kB pathway

Abstract: Objective: This study explored the effects and mechanisms of Huangqi Guizhi Wuwu Decoction on chemotherapy-induced neuropathic pain (CINP). Methods: Bodyweight and related behavioral testing of the rat model were utilized to investigate the effects of Huangqi Guizhi Wuwu Decoction on CINP. ELISA was used to measure the levels of TNF-α, IL-1β, and IL-6, in the serum of chronic CINP rats. Immunohistochemistry and Western blot analysis were performed to detect the expression of MAPK pathway related-proteins namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…[42] NF-κB p65 is translocated into the nucleus by activating p38 MAPK signaling, resulting in the development of NP. [43] In our study, the activation of p38 MAPK and NF-κB was observed in the spinal dorsal horn of CCI-treated rats, in line with Dai's research. [44] Following the administration of the GPR39 agonist, the p38 MAPK/NF-κB signaling was markedly repressed, implying that the impact of the GPR39 agonist on the activation of microglia in CCI-treated rats might be regulated by suppressing the p38 MAPK/NF-κB signaling pathway.…”
Section: Discussionsupporting
confidence: 89%
“…[42] NF-κB p65 is translocated into the nucleus by activating p38 MAPK signaling, resulting in the development of NP. [43] In our study, the activation of p38 MAPK and NF-κB was observed in the spinal dorsal horn of CCI-treated rats, in line with Dai's research. [44] Following the administration of the GPR39 agonist, the p38 MAPK/NF-κB signaling was markedly repressed, implying that the impact of the GPR39 agonist on the activation of microglia in CCI-treated rats might be regulated by suppressing the p38 MAPK/NF-κB signaling pathway.…”
Section: Discussionsupporting
confidence: 89%
“…Traditional Chinese medicine categorizes DVT as “pulse obstruction” and “blood stasis.” [ 11 ] Sun Simiao, a renowned Chinese physician over a thousand years ago, noted in Qian Jin Bei Ji Yao Fang that poor blood circulation is the root cause of thrombosis: “if qi and blood are stagnant, there will be pain; if the pulse is blocked, there will be swelling, and if stagnation persists for a long time, heat will arise.” HQGZWWD is composed of five traditional Chinese medicines: Huangqi ( Hedysarum multijugum maxim , HM), Guizhi ( Cinnamomi Ramulus , CR), Baishao ( Paeoniae Radix Alba , PA), Shengjiang ( Zingiber officinale Roscoe , ZR), and Dazao (Jujubae Fructus , JF) [ 12 ]. HQGZWWD is a medicinal formula that promotes blood circulation and nourishes the qi; this was reported by Zhang Zhongjing, a medical expert from the Eastern Han Dynasty (approximately 154–219 AD), in his book “Jin Gui Yao Lue” almost 2000 years ago [ 13 ]. Additionally, various medical books such as “San Yin Ji Yi Bing Zheng Fang Lun” from the Southern Song Dynasty (1174 AD), “Zheng Zhi Zhun Sheng: Lei Fang” from the Ming Dynasty (1602 AD) and “Yi Fang Ji Jie” from the Qing Dynasty recorded the effectiveness of HQGZWWD in treating DVT.…”
Section: Introductionmentioning
confidence: 99%
“…138 Oxaliplatin is one of the cancer-related drugs used in treating colon and rectal cancer that can lead to neuropathic pain. 139 The main mechanism of neuropathic pain is under debate. In vivo studies have suggested several mechanisms for neuropathic pain, but these mechanisms in humans may differ completely.…”
Section: The Role Of Micrornas In Oxaliplatin-induced Neuropathic Painmentioning
confidence: 99%